Physiological Dysregulation, Frailty, and Impacts on Adverse Health and Functional Outcomes - Lu, Yanxia; Gwee, Xinyi; Chua, Denise Q. L.; Tan, Crystal T. Y.; Yap, Keng Bee; Larbi, Anis; Ng, Tze Pin (Frontiers in Medicine, 2021)
Background: Multi-system physiological dysregulation (PD) may represent a biological endo-phenotype of clinical frailty. We investigated the co-occurrence of PD with physical frailty and its contributions to the known impact of frailty on adverse health outcomes. Methods: Data of 2725 participants from the Singapore Longitudinal Ageing Studies (SLAS-2), included baseline measures of physical frailty and PD derived from Mahalanobis distance (Dm) value of 23 blood biomarkers. We analyzed their concurrent association and their impacts on 9-year mortality, MMSE cognition, GDS depression, number of medications, disability and hospitalization at baseline and follow up (mean 4.5 years). Results: Global PD (Log10Dm, mean=1.24, SD=0.24) was significantly but weakly associated with pre-frailty-and-frailty. Controlling for age, sex and education, pre-frailty-and-frailty (HR=2.12, 95%CI=1.51-3.00) and PD (HR=3.88, 95%CI=2.15-6.98) predicted mortality. Together in the same model, mortality HR associated with pre-frailty-and-frailty (HR=1.83, 95%CI=1.22-2.73) and PD (HR=3.06, 95%CI=1.60-5.85) were reduced after additionally adding global PD to the prediction model. The predictive accuracy for mortality were both approximately the same (PD: AUC=0.62, frailty: AUC=0.64), but AUC was significantly increased to 0.68 when combined (p < 0.001). Taken into account in the same model, frailty remained significantly associated with all health and functional outcomes, and PD was significantly associated with only MMSE, disability and medications used. In secondary analyses, there were mixed associations of system-specific PDs with frailty and different adverse outcomes. Conclusions: Co-existing PD and physical frailty independently predict mortality and functional and health outcomes, with increased predictive accuracy when combined. PD appears to be a valid representation of a biological endo-phenotype of frailty, and the potential utility of such subclinical measures of frailty could be further studied.